Riesgos Sociales que afrontan las Familias que han Inmigrado de Venezuela y que Condicionan la Inclusión Social en el Cantón Babahoyo, en el año 2023. - Solano Calvopiña, Bartolomé Salomón (2023)
Human mobility has been very pronounced in recent years,it has had great impact in several Latin American countries due to various factors, Ecuador is one of the destination countries with a considerable human solidarity because offers a reception of population from each Latinamarican countries, receiving people in a state of vulnerability that have settled in several cities of this country. The majority of immigrant families, even before traveling to a certain country, already have a complicated livelihood, this is the reason why they seek to leave the country where they reside to try to achieve a better quality of life, but in the process they stumble upon external principles that complicate them, so they must find multiple options during their transit. This degree work is carried out with the objective of determining the social risks that families who have immigrated from Venezuela have had to face, identifying their socioeconomic situation and explaining what are the main conditions that prevent them from social inclusion in the city of Babahoyo during the year 2023, with the sole purpose of improving their quality of life and changing the vision we have of human mobility, giving the viewer another perspective on the subject so as not to establish wrong stereotypes of these people, whether due to their way of dressing, their skin tone, age or physical deficiencies, which causes exclusion from society, causing low self-esteem and fragility to abuse, whether physical or verbal, which can cause illicit acts such as drug addiction, theft or prostitution. In the city of Babahoyo, there is no statistical data about the Venezuelan immigrant population during the last two years. At the beginning of the year 2023 the Ministry of Economic and Social Inclusion made a census obtaining as a result 257 families living in that citiy, so with these data we were able to conduct this study with a mixed qualitative and quantitative approach of descriptive - explanatory type.